2023
DOI: 10.1021/acs.jproteome.3c00178
|View full text |Cite
|
Sign up to set email alerts
|

Does the Ubiquitination Degradation Pathway Really Reach inside of the Chloroplast? A Re-Evaluation of Mass Spectrometry-Based Assignments of Ubiquitination

Abstract: A recent paper in Science Advances by Sun et al. claims that intrachloroplast proteins in the model plant Arabidopsis can be polyubiquitinated and then extracted into the cytosol for subsequent degradation by the proteasome. Most of this conclusion hinges on several sets of mass spectrometry (MS) data. If the proposed results and conclusion are true, this would be a major change in the proteolysis/proteostasis field, breaking the long-standing dogma that there are no polyubiquitination mechanisms within chloro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 67 publications
(205 reference statements)
0
1
0
Order By: Relevance
“…With the current findings, it remains unclear whether PDX proteins are actually ubiquitinated in planta since our data did not support the UPP as primary reason for PDX instabilities. Recently, van Wijk et al [77] showed that alkylating agents, such as iodoacetamide, can result in artifactual acetamide signatures that are not distinguishable from ubiquitination signatures in mass spectrometry-based analysis. Since both Manzano et al [23] and Saracco et al [24] used iodoacetamide in their works, it opens up the possibility that at least in part some of the proteins identified are false positives and artifacts of the experimental approach.…”
Section: Discussionmentioning
confidence: 99%
“…With the current findings, it remains unclear whether PDX proteins are actually ubiquitinated in planta since our data did not support the UPP as primary reason for PDX instabilities. Recently, van Wijk et al [77] showed that alkylating agents, such as iodoacetamide, can result in artifactual acetamide signatures that are not distinguishable from ubiquitination signatures in mass spectrometry-based analysis. Since both Manzano et al [23] and Saracco et al [24] used iodoacetamide in their works, it opens up the possibility that at least in part some of the proteins identified are false positives and artifacts of the experimental approach.…”
Section: Discussionmentioning
confidence: 99%